Non-Western Nations and the Liberal International Order - Govella, Kristi (Taylor & Francis, 2026)
Given the increasing presence of non-Western nations in global affairs, Hiro Katsumata and Hiroki Kusano explore their responses to the backlash taking place in the West against the global spread of liberalism – against the global spread of free trade, multilateral institutions, and liberal-democratic politics. Katsumata and Kusano concentrate on the cases of Egypt, Brazil, Japan, ASEAN members, Russia, and China. Mounted by these non-Western nations are three kinds of responses: illiberal bandwagoning, counter-backlash, and thirdway charting. Each of these responses inevitably has significant consequences for the fate of the existing liberal international order established and sustained by the Western countries in the post-war era, either accelerating the collapse of this order by causing additional damage to it, or putting the brakes on its collapse by giving support to it. An invaluable resource for scholars in International Relations and Comparative Politics. Chapter 4 of this book is freely available as a downloadable Open Access PDF at http://www.taylorfrancis.com under a Creative Commons Attribution-Non Commercial-No Derivatives (CC BY-NC-ND) 4.0 license.